Implementasi Nilai-Nilai Etis dalam Program KKN-PPM UGM (Studi Kasus di Desa Wonocepokoayu, Kecamatan Senduro, Kabupaten Lumajang, Jawa Timur) - Ridwan Ahmad Sukri; Muhammad Haris Naufal; Mohammad Rayhan Alfin Syahri (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
This writing is a reflection on the activities of the community service program, namely the Community Service Program of Universitas Gadjah Mada in Wonocepokoayu Village, Senduro District, Lumajang Regency, East Java Province. The implementation of the KKN program in this village was successfully supported by the application of ethical values. The methods used in solving the problem are social mapping, field observations, information search, preparation of program plans and implementation, and periodic evaluations. Programs have been widely implemented to solve problems related to improving the level of welfare. Implementing ethical values is the main thing that determines the success of KKN activities in the view of the community. Programs that have been implemented to solve existing problems, which of course is strengthened by ethical practices: optimizing grafting of mangosteen plants, making maps of height and slope, socializing the importance of sanitary pens for livestock, identifying irrigation sources, socializing on saving from an early age, making land use maps, socializing goat health, infographics superior agricultural commodities, socialization of medicinal plants, Science Project, Improvement of nutrition, making livestock distribution maps, making internet content about village potential, socializing integrated marketing systems, making Village Profile videos, 38) Making video tutorials on making liquid fertilizer, making liquid organic fertilizer and too many others to mention one by one. An inseparable part of achieving the success of this Community Service Program is the application of ethical values by service participants in community life such as discipline, cooperation, honesty, openness, egalitarianism, respect for self and others, maintaining the goodwill of the campus community, simplicity. The result is better changes in society after the Community Service Program of UGM. In conclusion. There is synergy between skills, knowledge, and the application of ethical values to achieve success in Community Service Programs.